1983
DOI: 10.1192/bjp.142.6.618
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Post-Partum Psychosis

Abstract: Two women who both experienced a psychotic illness after each of three consecutive pregnancies are described. Subjects who are at high risk for post-partum psychotic breakdown offer an almost unique opportunity for prospective tests of hypotheses about the aetiology of severe mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Prospective investigations of such women through pregnancy and the postpartum period therefore permit rigorous evaluation of putative aetiological mechanisms. 3 Of all the endocrine changes taking place after parturition, the sharp fall in circulating sex steroid hormone concentrations is perhaps most likely to contribute to the precipitation of psychosis in predisposed women. Unlike most other hormones steroids have easy access to the brain and concentrations of oestradiol and progesterone in plasma and cerebrospinal fluid are highly correlated.4 Recent research has shown that oestrogens modulate the function of monoaminergic and, in particular, dopaminergic neurotransmitter systems in the central nervous system.56 Abnormalities of dopaminergic neurotransmission have been implicated in both schizophrenic and manic depressive illness, and Cookson has proposed that puerperal psychosis is triggered by the effects of postpartum oestrogen withdrawal on central dopaminergic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective investigations of such women through pregnancy and the postpartum period therefore permit rigorous evaluation of putative aetiological mechanisms. 3 Of all the endocrine changes taking place after parturition, the sharp fall in circulating sex steroid hormone concentrations is perhaps most likely to contribute to the precipitation of psychosis in predisposed women. Unlike most other hormones steroids have easy access to the brain and concentrations of oestradiol and progesterone in plasma and cerebrospinal fluid are highly correlated.4 Recent research has shown that oestrogens modulate the function of monoaminergic and, in particular, dopaminergic neurotransmitter systems in the central nervous system.56 Abnormalities of dopaminergic neurotransmission have been implicated in both schizophrenic and manic depressive illness, and Cookson has proposed that puerperal psychosis is triggered by the effects of postpartum oestrogen withdrawal on central dopaminergic functions.…”
Section: Introductionmentioning
confidence: 99%